(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
This paper presents the experimental and analytical results of the contribution of carbon fibre reinforced polymer (CFRP) laminates to the shear strength of RC beams. To assess the efficiency of the carbon fibre reinforced polymer (CFRP) laminates on the strengthened specimens, twelve identical beams of cross-sectional dimensions 150x150x750mm were cast, out of which three are un-strengthened and nine were strengthened with U-wrap strips at 100 mm away from each support at varying CFRP laminates layers of single, double and triple amounts. The prepared specimens were subjected to a three-point bending test. The results obtained revealed that the CFRP laminate increased the shear strength of the strengthened specimens over the control (un-strengthened) by 35.06%, 54.40% and 69.30% for single, double and triple layers of CFRP laminate respectively. The experimental results was also compared with the analytical results obtained based on the equation proposed by Khalifa et al., 1998. The analytical results obtained from the equation closely agreed with the experimental results. Therefore, it implies that the CFRP has the potentials of strengthening shear defiant RC beams.